2015
DOI: 10.1002/stem.2239
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical tissue-derived cells rescue retinal pigment epithelium dysfunction in retinal degeneration

Abstract: Retinal pigment epithelium (RPE) cells perform many functions crucial for retinal preservation and vision. RPE cell dysfunction results in various retinal degenerative diseases, such as retinitis pigmentosa and age-related macular degeneration (AMD). Currently, there are no effective treatments for retinal degeneration except for a small percentage of individuals with exudative AMD. Cell therapies targeting RPE cells are being developed in the clinic for the treatment of retinal degeneration. Subretinal inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 89 publications
(146 reference statements)
0
33
0
Order By: Relevance
“…The most important finding of the current study is to unravel NDRG2 as the molecular hallmark of photoreceptor-specific cell viability, which was confirmed not only in vitro but also in vivo in retinal degeneration and treatment. In fact, there is a multitude of treatment strategies and compounds that at least partially prevent retinal degeneration in animal models, including the calcium channel blocker D-diltiazem 56 , 57 , various antioxidants 24 , 58 , caspase inhibitors 59 , 60 , multiple neuroprotective agents including NAM 35 , 36 and other neurotrophic cytokines 61 , apoptotic gene therapies 62 , 63 , and the recent stem cell transplantation 64 , 65 . Nevertheless, while retinal degeneration in preclinical studies could be effectively prevented, there does not seem to be a single treatment available at present that rescues photoreceptor cell damages in human 66 , 67 .…”
Section: Discussionmentioning
confidence: 99%
“…The most important finding of the current study is to unravel NDRG2 as the molecular hallmark of photoreceptor-specific cell viability, which was confirmed not only in vitro but also in vivo in retinal degeneration and treatment. In fact, there is a multitude of treatment strategies and compounds that at least partially prevent retinal degeneration in animal models, including the calcium channel blocker D-diltiazem 56 , 57 , various antioxidants 24 , 58 , caspase inhibitors 59 , 60 , multiple neuroprotective agents including NAM 35 , 36 and other neurotrophic cytokines 61 , apoptotic gene therapies 62 , 63 , and the recent stem cell transplantation 64 , 65 . Nevertheless, while retinal degeneration in preclinical studies could be effectively prevented, there does not seem to be a single treatment available at present that rescues photoreceptor cell damages in human 66 , 67 .…”
Section: Discussionmentioning
confidence: 99%
“…MSC‐secreted factors activate prolife signal transduction pathways in preapoptotic cells that are jeopardized by metabolic dysregulation from oxygen, glucose, or nutrient deprivation . Ex vivo assays showed that MSC‐CdM supports photoreceptor survival ex vivo and enhances RPE internalization of POSs , with an increase in RPE metabolic viability (Fig. 6C, 6D).…”
Section: Discussionmentioning
confidence: 93%
“…6C, 6D). Rat MSCs have been shown to secrete BDNF , the transcriptional silencing of which , or antibody neutralization in MSC‐CdM (Fig. 6M), reduced RPE phagocytosis ability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Subsequent in vitro studies showed that palucorcel was capable of rescuing RPE phagocytic dysfunction, promoting excitatory synaptic connectivity, enhancing neuronal survival, and enhancing neurite outgrowth via paracrine signaling pathways. 19,20 A recent phase 1/2a study evaluated the administration of palucorcel in 35 adults, 50 years of age and older, with bilateral GA secondary to AMD. A microcatheter delivery system (iTrack 275; iScience, Inc., Menlo Park, CA, USA) was used in conjunction with an ab externo surgical approach to access the subretinal space.…”
mentioning
confidence: 99%